Audit Kode Klinis Pasien Rawat Inap Jaminanan BPJS Kesehatan Di Rumah Sakit Tipe C Dan D Wilayah DIY - Hosizah, Hosizah; Puspita Ningsih, Kori; Nisak, Umi Khoirun; Widjaja, Lily (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
The quality of diagnosis codes is an important part of the hospital management level. The impact of a lack of quality diagnosis codes is the potential to reduce hospital income. A clinical coding audit needs to be conducted to review and analyze discovered errors and attempt to trace their source. The purpose of this research is to audit the code. The research approach was carried out through a quantitative descriptive approach. The research population was inpatient medical records of BPJS Health patients. Sample calculations use Slovin, with a margin of error of 10%. In this study, the clinical coding audit involved 3 coders in each hospital, coding experts from senior practitioners from Type B Hospitals and experts from academics. The results of the clinical code audit showed that the timeliness aspect was 100%, accuracy was 92.5%, completeness was 91.0%, relevance, and legitimacy were 87.5% each, while the lowest was in the reliability aspect at 80.0%. The results of the legibility aspect are in line with the results of relevance. This shows that determining clinical codes for case mix purposes must be supported by complete documentation of the patient's medical records.